1984
DOI: 10.1007/bf01966787
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the physiological significance of cimetidine interactions with copper and zinc in biofluids as based on the computer-simulated distribution of the involved complexes at therapeutic levels of the drug

Abstract: The hypothesis was formerly put forward that the main therapeutic action of cimetidine (the histamine H2-receptor antagonist marketed as Tagamet) as well as some of its side effects might be mediated by its interactions with essential metal ions. The present paper reports the potentiometric study of the coordination of the drug with copper(II) and zinc(II) in NaCl 0.15 mol dm-3 at 37 degrees C. Special attention was paid to copper complexes, due to (i) the involvement of cimetidine in rheumatoid arthritis evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The standard stock solution of zinc chloride in diluted hydrochloric acid was prepared from crystals supplied by Merck as a 'pro analysi' product, and was titrated for its metal and mineral acid contents as described earlier [11].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The standard stock solution of zinc chloride in diluted hydrochloric acid was prepared from crystals supplied by Merck as a 'pro analysi' product, and was titrated for its metal and mineral acid contents as described earlier [11].…”
Section: Methodsmentioning
confidence: 99%
“…The titration unit was similar to that previously described [11,17,18]. The evolution of the e.m.f, of an electrochemical cell of the type G.E./Antibiotic, Zn 2 § NaC1 (0.15 mol.dm-3)/NaCt (satd) /Hg2Clz-Hg (1) was monitored by a digital mV-meter Beckman Model 4500.…”
Section: Technique and Equipmentmentioning
confidence: 99%
See 2 more Smart Citations
“…From computer simulations, it was possible to verify that cimetidine did not influence zinc or copper bio-availability in the blood plasma at therapeutic levels of the drug. 12 Another study, performed for a series of effective H 2 antagonists of histamine has shown that all ligands containing a guanidinethiazole fragment coordinate Cu II ions through two nitrogen donors. The adjacent thioether sulfur may also be involved in metal-ion binding, contributing to the stabilities of the complexes formed.…”
Section: Introductionmentioning
confidence: 99%